Stability enhancement in organic solar cells by incorporating V2O5 nanoparticles in the hole transport layer. Issue 55 (20th May 2016) - Rafique, Saqib; Abdullah, Shahino Mah; Mahmoud, Waleed E.; Al-Ghamdi, Attieh A.; Sulaiman, Khaulah
Abstract : The synthesis of vanadium pentaoxide (V2 O5 ) nanoparticles by a hydrothermal method and their utilization in a PEDOT:PSS buffer layer in a PCDTBT:PC71 BM device structure is demonstrated. Abstract : The synthesis of vanadium pentaoxide (V2 O5 ) nanoparticles by a hydrothermal method and their utilization in a PEDOT:PSS buffer layer in a PCDTBT:PC71 BM device structure is demonstrated. V2 O5 nanoparticles were dispersed in the PEDOT:PSS hole transport layer (HTL) in normal architecture bulk heterojunction (BHJ) solar cells. The device performance for both pure PEDOT:PSS and hybrid HTLs were studied and demonstrated to effectively work in bulk heterojunction organic solar cells (BHJ OSCs). From the stability test initially for one week and subsequently for another three weeks, it was confirmed that the OSC device with the incorporation of V2 O5 nanoparticles in the standard HTL leads to a decrease in device degradation and significantly improves the lifetime as compared to the standard HTL based device. Moreover, the hybrid HTL exhibits better optical properties and a relatively stable band gap as compared to its pristine PEDOT:PSS counterpart. Our results indicate that V2 O5 could be a simple addition into the PEDOT:PSS layer to overcome its stability and degradation issues leading to an effective HTL in BHJ OSCs.